algebra
posted by april .
Solve the question for both the exact irrational root and its rational approximation to the nearest tenth. sqrt 2 over 3 s + 1 = sqrt 23
q=
Respond to this Question
Similar Questions

Algebra
Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide … 
math calculus please help!
l = lim as x approaches 0 of x/(the square root of (1+x)  the square root of (1x) decide whether: l=1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x>0 x/[sqrt(1+x)  sqrt(1x)] ? 
math
determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the … 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
Algebra
SIMPLIFY: ROOT 0F 7 * ROOT OF 14 SIMPLIFY: ROOT OF 1/5 EVALUATE, IF POSSIBLE: ROOT OF 9/16 (I GOT 3/4 BUT I WAS NOT SURE IF THAT WAS CORRECT OR NOT) SIMPLIFY. ASSUME X REPRESENTS A POSITIVE NUMBER: ROOT OF 45X^4 ROOT 0F 7 * ROOT OF … 
algebra
simplify: square root of 5 + square root of 20  square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20  sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5)  sqrt (3*9) + sqrt (49*3) = 3 sqrt 5  3 sqrt 3 + 7 … 
Math
Here is the question: Is the product of two irrational numbers always an irrational number? 
algebra
Solve the question for both the exact irrational root and its rational approximation to the nearest tenth 3h + sqrt 2 = sqrt 5 
algebra
a+ sqrt 2 = 7 Solve the question for both the exact irrational root and its rational approximation to the nearest tenth. THANK YOU FOR YOUR TIME AND HELP 
Surds
Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed me to do this next: Square both sides..so.. 4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4 I do not understand where the 2 come from ..and why do we need to multiply …